Monitoring the Effect of Disinfection Methods on Mycoplasma gallisepticum in Commercial Layer Farms - Khalil, Maged M.; Alfateeh, Nayera M.; Kaoud , Hussein A. (International Journal of Poultry Science, 2022)
Background and Objective: It is important for poultry owners to control disinfectants resistance of Mycoplasma gallisepticum circulating amongst poultry farms. On a field level among poultry flocks a survey study was conducted to identify and to estimate the effects of the most common poultry pathogens (Mycoplasma gallisepticum) on production performance of commercial layer hens and the efficacy of the most common disinfectants against Mycoplasma gallisepticum was determined through traditional and new methods of application against MG strain isolated from commercial layer farms in Egypt and recorded in Gen-Bank. Materials and Methods: A survey study was carried out to identify and to estimate the effects of Mycoplasma gallisepticum on production performance of 15 commercial layer flocks. In addition, the efficacy of some commercially available disinfectants against Mycoplasma gallisepticum with different application methods was also monitored. Results: The results showed that: (1) The prevalence of M. gallisepticum (33.3%) and mortality rate (12%) was high in the flocks at 78 weeks of age and the current egg-production performance was also significantly reduced (p<0.05). (2) MG isolate accessed on Gen-Bank and coded as; MZ826700 , 26 bp DNA linear BCT 30-SEP-2021, DEFINITION Mycoplasma gallisepticum strain EGY2021 mgc2 gene, partial cds. ACCESSION MZ826700-authers: Alfeteehy, N.M., Mohamed, M. and Kaoud, H.A. (3) Fogging method showed the highest reduction in Mycoplasma gallisepticum populations. Conclusion: Mycoplasma gallisepticum infection leads to tremendous economic losses in poultry production as a result of decreased hatchability, egg production and mortalities; it is evident that, fogging will increase the efficacy of the used disinfectants for 15 min contact of exposure time.